The digital interactivity of US think tanks’ communications - Elizabet Castillero-Ostio; Andrea Moreno-Cabanillas; Leticia Rodríguez-Fernández (Frontiers in Political Science)
The communicative actions of think tanks play a fundamental role in shaping public policies and social discourse, with their capacity for interaction with diverse audiences being vital to maximizing their influence. This study conducts a quantitative content analysis of the communication tools utilized on the websites of the 25 most influential think tanks in North America, as identified in McGann's (2021) report. It assesses the degree of interactivity fostered by these platforms in their relationship with users, revealing that, while the interactivity of one-way tools is notably high, the options for bidirectional interaction remain at a moderate level, characterized by a predominance of asymmetric resources. The findings suggest that, despite effective information transmission, think tanks must adopt more dynamic and participatory communication strategies that promote genuine dialogue and greater collaboration, thereby adapting to a constantly evolving digital environment that demands stronger connections with diverse audiences.